The discursive construction of spiritual values and cultural standards in Sang Pemimpi Film - Rustono Farady Marta; Changsong Wang; Al Ryanne Gabonada Gatcho; Florence Yulisinta; Hana Panggabean (International Journal of Visual and Performing Arts, 2023)
Spirituality is a contentious human phenomenon that encompasses personal, sociocultural, and transcendent interconnection. In Indonesian society, spiritual experiences are often associated with religion. They are also part of the cultural standards, the way of thinking, feeling, and behaving shared by most of a culture's members. This research aims to examine the spiritual and cultural values of Belitung's Muslim society through the Sang Pemimpi film. The research method in this study was critical discourse analysis, a qualitative approach based on a critical paradigm. This study combines Theo van Leeuwen's critical and multimodality discourse analysis techniques. Spiritual values and cultural standards are used as theoretical elements. The character in the film's text with the background of the Muslim society and the Belitung people's culture is the focus of this study. According to the film analysis, spirituality is formed by socio-cultural interactions in people's daily lives. The Muslim community in Belitung adapts well to religious and cultural differences in their social relationships with other ethnic groups, including the Chinese ethnic groups. According to the findings of this study, religiosity and communal domains are the aspects that appear the most in the film.